Financial and Management Accounting: An Introduction - Weetman, Pauline (Slovakia Pearson, 2019)
Written by an expert teacher in Accounting, the eighth edition of this well-respected text retains all the features that have contributed to the book's popularity: focus on the accounting equation, an even greater range of student activities throughout each chapter, a clear and accessible writing style, and extensive use of real-world case studies. With a strong emphasis on the 2018 Conceptual Framework of the International Accounting Standards Board, Financial & Management Accounting: An Introduction guides students in understanding the 'why' and not just the 'what' of financial and management accounting. Key features: Definitions and terminology are aligned with the 2018 IASB Conceptual Framework New case studies giving examples from real-world companies Activities aligned to each section of a chapter to encourage students to explore and consider issues from different angles Expanded for this edition, experience-driven conversations between two managers are included throughout, updated with an even more practical emphasis Coverage on fair value throughout Exploration of the Strategic Report and Directors' Report Fully up-to-date with International Financial Reporting Standards (IFRS) Focuses on specific knowledge outcomes, with end-of-chapter self-evaluation Questions are graded according to difficulty to test student understanding Financial & Management Accounting: An Introduction is a core textbook for undergraduates on Business Studies degrees, undergraduates on Accounting courses, students studying accounting for MBA and postgraduate courses, and professional courses where accounting is introduced for the first time.
Keywords: Finance; Accounting; Management Accounting; Management; Textbooks; (UGB106) Introduction to Management Accounting